Orofacial granulomatosis: A disease or a concealed warning.?? - Priya Anil Bhagde; Jyoti D Bhavthankar; Mandakini Mandale (Wolters Kluwer Medknow Publications, 2017)
Granulomatosis is any condition characterized by the formation of multiple nodules or granulomas in the soft tissues. Differential diagnosis for orofacial region includes a wide spectrum of diseases, but most of these lesions present histopathologically as noncaseating granulomas, giving a nonspecific depiction and leading to a diagnostic impasse. In the absence of any diagnosable entity, the disease is labelled as "orofacial granulomatosis". A nine-year-old girl child reported with recurrent gingival enlargement and persistent macrochelia which histopathologically presented as noncaseating granulomas. The disease was progressive raising the suspicion of being oral manifestation of a systemic disorder such as Sarcoidosis or Crohn's disease. This paper throws some light on this rare entity and reports rarer features of this disease, like eye involvement and staphylococcal mucositis in the case report.